The problems of localization in videogames based on «Uncharted» game series: the perception effect as a neurolinguistics aspects; Проблемы геологии и освоения недр; Т. 2 - Istigecheva A. V. (Проблемы межъязыковой профессиональной коммуникации в условиях глобализации, 2022)
Заглавие с экрана